Composition and genesis of the organic matter in the bottom sediments of the East Siberian Sea. - Vetrov, Alexander A; Semiletov, Igor P; Dudarev, Oleg V; Peresypkin, Valery I; Charkin, Alexander N (PANGAEA, 2008)
The chemical composition of organic matter (Corg, Norg, d13C, d1SN, and n-alkanes) was studied in the top layer of bottom sediments of the East Siberian Sea. Possible ways were proposed to estimate the amount of the terrigenous component in their organic matter (OM). The fraction of terrigenous OM estimated by the combined use of genetic indicators varied from 15% in the eastern part of the sea, near the Long Strait, to 95% in the estuaries of the Indigirka and Kolyma rivers, averaging 62% over the sea area.
(Table) Carbon, nitrogen and n-alkane content and isotopic composition of bottom sediments obtained in the East Siberian Sea
Keywords: Archive of Ocean Data; ARCOD; Carbon, organic, total; Carbon/Nitrogen ratio; Carbon Preference Index, n-Alkanes; Continuous Flow Isotope Ratio Mass Spectrometry (CF/IRMS); DEPTH, sediment/rock; East Siberian Sea; Gas chromatography; i-C19/C17 ratio; i-C19/i-C20 ratio; i-C20/C18 ratio; IK04-102; IK04-106; IK04-112; IK04-25; IK04-30; IK04-34; IK04-38; IK04-40; IK04-44; IK04-46; IK04-49; IK04-51; IK04-55; IK04-60; IK04-62; IK04-64; IK04-66; IK04-68; IK04-72; IK04-MT04; Ivan Kireev-2004; Ivan Kireyev; n-Alkane, total per unit sediment mass; Nitrogen, total; Sediment type; Station label; Sum(C10-C22)/sum(C23-C40) n-alkanes ratio; Sum even numbered n-alkanes; Sum n-alkanes C10-C17; Sum n-alkanes C10-C22; Sum n-alkanes C18-C22; Sum n-alkanes C20-C24; Sum n-alkanes C23-C35; Sum n-alkanes C23-C40; Sum odd numbered n-alkanes; van Veen Grab; VGRAB; Water content, dry mass; δ13C; δ15N